Bifurcation of Positive Solutions for a Class of Boundary Value Problems of Fractional Differential Inclusions - Yansheng Liu; Huimin Yu (Abstract and Applied Analysis)
Using Krein-Rutman theorem, topological degree theory, and bifurcation techniques, this paper investigates the existence of positive solutions for a class of boundary value problems of fractional differential inclusions.